Origin of Early Cretaceous magmatism and its linkage with Cu–Fe–Au skarn mineralization in the Tonglushan ore field, eastern China: Evidence from whole-rock, zircon, and apatite geochemistry - Ming Zhang; Xiangzhou Li; Yanyan Zhao; Shichao Shang; Jiaming Zhou; Wan Huang; Yiheng Liu; Ziqing Yan; Xiaoyang Liu; Jun Tan (Lithos, 2026)

A kidney-targeted MOF nanozyme combats calcium oxalate crystal-induced kidney injury - Xuhong He; Min Zhou; Zhengxin Liang; Shiyi Jin; Kunze Yu; Longxiyu Meng; Zhicong Tan; Jinming Xu; Jiaju Xu; Chongjun Xiang; Jingchao Wei; Wenjun Gao; et al. (Chemical Engineering Journal, 2026)

Sex-specific differences in cadmium accumulation and responses in the freshwater snail Cipangopaludina cathayensis - Wei Jinyou; Xiang Shanshan; Yu Jing; Li Linli; Tan Haizhen; Ye Quanqing; Yang Liu; Deng Yufan; Cui Jiaming; Wu Zhengjun; Jiang Jiaoyun (Chemico-Biological Interactions, 2026)

Garnet microtextures and geochemistry of the Tonglushan Cu–Fe–Au skarn deposit (Edong district): Constraints on fluid evolution and skarn mineralization - Ming Zhang; Xiangzhou Li; Ziqing Yan; Shichao Shang; Wan Huang; Yanyan Zhao; Jiaming Zhou; Xiaoyang Liu; Jingui Huang; Jun Tan (Journal of Geochemical Exploration, 2026)

Fully coupled numerical model of moored structures-mooring line-ice ridge interaction - Jiaming Chen; Shengjie Rui; Sen Han; Shifeng Ding; Jie Tan; Li Zhou (Ocean Engineering, 2026)

In-situ sulfur element-induced heterogeneous interface engineering for high-performance supercapacitors - Mingzhe Shan; Yi Jiang; Ruixiang Xu; Bin Cai; Yi Gao; Heju Zhao; Jiaming Wang; Yaozeng Lu; Xiqing Song; Surong Tan; Yishan Yuan; Zining Li; et al. (Chemical Engineering Journal, 2026)

Design of a green certificate differentiated issuance mechanism based on renewable energy enterprises subsidy perspective: A case study of China - Qinliang Tan; Chaofan Shi; Jiabin Zeng; Zihan Jin; Yihong Ding; Jiaming He; Guangyu Qin (Energy Policy, 2026)

The links between Na/K ratios in eolian sands and mean annual precipitation in the deserts of arid region, northern China - Jiaqi Wang; Shipei Dong; Zhuolun Li; Jiaming Qu; Yuhan Kuai; Dianjia Tan; Jie Luo (CATENA, 2025)

Role of adiabatic heating in winter warming over the Tibetan Plateau - Jiaming Tan; Meiyu Chang; Zouxing Lin; Zhiyan Zuo (Science China Earth Sciences, 2025)

Phytoextraction of Soil Cadmium by Vetiveria zizanioides Dead Shoots - Wenwen Li; Ning Liu; Xiaoling Tan; Ruoyao Shen; Jiaming Yu; Jie Li; Khateeb Hussain; Shiyong Yang (Bulletin of Environmental Contamination and Toxicology, 2025)

Study on the division method of the excavation disturbed zone in tunnels based on continuous-discontinuous theory - Jixu Zhang; Xiaodong Fu; Chao Tan; Yongqiang Zhou; Qian Sheng; Chen Xu; Jiaming Wu (Bulletin of Engineering Geology and the Environment, 2025)

Effects of chlorpyrifos stress on the Eriocheir sinensis suffering from Metschnikowia bicuspidata infection - Jiaming Dong; Yuanyuan Tan; Chengcheng Feng; Qingbiao Hu; Yanhong Zhao; Jie Bao; Hongbo Jiang (Aquaculture, 2025)

Chronic chlorpyrifos exposure induces oxidative stress, neurological damage, and hepatopancreas enrichment in Chinese mitten crab (Eriocheir sinensis) - Yuanyuan Tan; Jiaming Dong; Luyao Wang; Weining Li; Jie Bao; Hongbo Jiang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Noise reduction and analysis of leaf electrical signals of strap-leaved plants based on VMD-EWT - Jiaming Gu; Fangming Tian; Jingxiu Shi; Feng Tan (Computers and Electronics in Agriculture, 2024)

Construction of La1−xSrxNiO3/g-C3N4 type-Z heterojunctions with enhanced visible-light photocatalytic degradation of organic pollutants - Pengke Yu; Jiaxing Guo; Liang Guo; Yaqin Deng; Juntao Tan; Qunang Xu; Qingmao Zhang; Jiaming Li (Environmental Research, 2024)

The role of HMGB2 in the immune response of Nile tilapia (Oreochromis niloticus) to streptococcal infection - Yuhang Dong; Zhiqiang Zhang; Yongxiong Huang; Xuyan Tan; Xing Li; Meiling Huang; Jiaming Feng; Yu Huang; Jichang Jian (Fish & Shellfish Immunology, 2024)

Significantly enhancing high-temperature piezoelectric response and Tdr of BF-BT-based ceramics through multi-component optimization strategy - Huabin Yang; Jiaming Zhu; Xueting Wang; Qiuling Luo; Hua Tan; Haibo Zhang; Jiwen Xu; Qiaohong Chen (Chemical Engineering Journal, 2024)

The New Roles of traf6 Gene Involved in the Development of Zebrafish Liver and Gonads - Hongyan Xu; Wenzhuo Ban; Jiaming Tian; Jianfei Xu; Zhimin Tan; Sendong Li; Kaili Chen; Mi Ou; Kaibin Li (Marine Biotechnology, 2024)

Effect of temperature on the occurrence of Metschnikowia bicuspidata disease in Eriocheir sinensis - Hongbo Jiang; Gangnan Cao; Jie Bao; Chengcheng Feng; Xiaodong Li; Yuanyuan Tan; Jiaming Dong; Qijun Chen (Aquaculture, 2024)

Tectonomagmatic setting and magmatic Cu-PGE metallogeny during the late Neoproterozoic in the Eastern Kunlun Orogen, NW China: Insights from the Hatu Cu-Pt-Pd-bearing mafic-ultramafic intrusion - Liang Li; Fengyue Sun; Li Wang; Yajing Zhang; Chao Wang; Ye Qian; Tuofei Zhao; Jiaming Yan; Shucheng Tan (Precambrian Research, 2023)

Effects of Dietary Lentinus edodes Fermentation Supplementation on Digestive Enzyme Activity, Antioxidant Capacity and Morphology of the Liver and Intestine in Largemouth Bass (Micropterus salmoides) Fed High Plant Protein Diets - Jiaming Xu; Zhoulin Yu; Guangye Liu; Sijie Li; Guoyong Zhou; Hanhua Wang; Yewei Dong; Cuihong You; Weidong Bai; Meng Zhou; Yanhua Huang; Xiaohong Tan (Fishes, 2023)
This study evaluated the effect of Lentinus edodes fermentation (LEF) on digestive enzyme activity, antioxidant capacity and morphology of the liver and intestine in largemouth bass (Micropterus salmoides) fed high plant protein diets (HPPD). LEF was supplemented in HPPD with 0 g kg−1 (LEF0), 10 g kg−1 (LEF1), 20 g kg−1 (LEF2), 30 g kg−1 (LEF3), 40 g kg−1 (LEF4), 50 g kg−1 (LEF5), respectively, and then the six diets were fed to largemouth bass with a body weight of 28.8 ± 0.05 g for eight weeks. Juvenile fish were randomized into 6 groups and each group had 4 replicates with 40 fish. Dietary LEF supplementation alleviated the liver inflammatory reaction of largemouth bass caused by HPPD and improved liver morphology. Goblet cells multiplied and the gut muscle layer thickened after LEF supplementation. The LEF significantly increased amylase activity in the liver and intestine of largemouth bass in individual experimental groups. The LEF could increase the activity of catalase in the liver and intestine of largemouth bass (p

Analysis of droplet deposition and maize (Zea mays L.) growth control: Application of ethephon by small unmanned aerial vehicle and electric knapsack sprayer - Zhao Wang; Mujahid Hussain; Jiaming Yin; Mengying Yuan; You Mo; Mengping Quan; Liusheng Duan; Weiming Tan (Field Crops Research, 2023)

De novo assembly, transcriptome characterization, and simple sequence repeat marker development in duckweed Lemna gibba - Lili Fu; Zehong Ding; Anuwat Kumpeangkeaw; Deguan Tan; Bingying Han; Xuepiao Sun; Jiaming Zhang (Physiology and Molecular Biology of Plants, 2020)

Comparative morphology of in vivo and in vitro laticiferous cells and potential use of in vitro laticifers in early selection of rubber tree clones - Deguan Tan; Anuwat Kumpeangkeaw; Xuepiao Sun; Weiguo Li; Yiming Zhu; Jiaming Zhang (Trees, 2019)

Age-dependent and jasmonic acid-induced laticifer-cell differentiation in anther callus cultures of rubber tree - Deguan Tan; Xuepiao Sun; Jiaming Zhang (Planta, 2014)

Histochemical and immunohistochemical identification of laticifer cells in callus cultures derived from anthers of Hevea brasiliensis - Deguan Tan; Xuepiao Sun; Jiaming Zhang (Plant Cell Reports, 2011)